Politik Hukum Terhadap Qanun Nomor 6 Tahun 2014 Tentang Hukum Jinayah - Rahmiati, Rahmiati (Faculty of Law, Universitas Pattimura, 2020)
One of the provinces that get a portion of special autonomy is the province of Aceh. Privilege in Aceh include organizing the life of religion, culture, education, and the role of the clergy in the determination of regional policy. Laws enacted in Aceh is a law which is based on the teachings of Islam, namely: Syari teachings